Role of chitinase-like proteins in cancer - Kzhyshkowska, Julia; Yin, Shuiping; Liu, Tengfei (Biological chemistry, 2016)
Chitinase-like proteins (CLPs) are lectins combining properties of cytokines and growth factors. Human CLPs include YKL-40, YKL-39 and SI-CLP that are secreted by cancer cells, macrophages, neutrophils, synoviocytes, chondrocytes and other cells. The best investigated CLP in cancer is YKL-40. Serum and plasma levels of YKL-40 correlate with poor prognosis in breast, lung, prostate, liver, bladder, colon and other types of cancers. In combination with other circulating factors YKL-40 can be used as a predictive biomarker of cancer outcome. In experimental models YKL-40 supports tumor initiation through binding to RAGE, and is able to induce cancer cell proliferation via ERK1/2-MAPK pathway. YKL-40 supports tumor angiogenesis by interaction with syndecan-1 on endothelial cells and metastatic spread by stimulating production of pro-inflammatory and pro-invasive factors MMP9, CCL2 and CXCL2. CLPs induce production of pro- and anti-inflammatory cytokines and chemokines, and are potential modulators of inflammatory tumor microenvironment. Targeting YKL-40 using neutralizing antibodies exerts anti-cancer effect in preclinical animal models. Multifunctional role of CLPs in regulation of inflammation and intratumoral processes makes them attractive candidates for tumor therapy and immunomodulation. In this review we comprehensively analyze recent data about expression pattern, and involvement of human CLPs in cancer.